Nanozyme-based sensors for cancer diagnosis - Olga Guliy; Lev Dykman (Biosensors and Bioelectronics: X, 2024)
Many biosensor technologies that can precisely and sensitively identify biomarkers reflecting disease status are being developed to help with early cancer detection and anticancer treatment monitoring. The creation of sensors based on nanozymes is one of the novel approaches in the intricate diagnosis and treatment of cancers. Because natural enzyme sensors can be unstable and expensive, the use of nanozymes in biosensors offers a great substitute for this type of study. Nanozymes have a stable shelf life, great operational reliability, cheap cost, and outstanding catalytic activity. The technological approaches to generating nanozymes and their use in sensors are briefly described in the paper. A summary of the many kinds of biosensors based on diverse kinds of nanomaterials for the identification of cancer biomarkers is provided, along with a discussion of the latest developments and challenges in the field of nanozyme biosensors for use in cancer diagnosis.